Morphological analysis of the female reproductive system of Stenorhynchus seticornis (Brachyura: Inachoididae) and comparisons with other Majoidea. Issue 2 (8th April 2016) - Antunes, Mariana; Zara, Fernando José; López‐Greco, Laura S.; Negreiros‐Fransozo, Maria Lucia
Abstract: We examined the female reproductive system of the yellowline arrow crab Stenorhynchus seticornis by means of histological and histochemical techniques. Mature specimens obtained in the field were kept in the laboratory for mating experiments. After 24 h, newly mated females were dissected, and their reproductive trait routinely processed for embedding in historesin. The specimens examined each possessed a pair of kidney‐shaped seminal receptacles (SR), and these we classified as ventral type, based on the location of the oviduct opening. The mesodermal dorsal region (DR) of SR consisted of a stratified epithelium with scaly cells, while the ectodermal ventral region (VR) was composed of a simple epithelium covered by a cuticle. The oviduct opened at the transition region (TR) between DR and VR and had no velum. The simple epithelium of TR had more folds on the face of the oviduct opening. The vagina exhibited the same features as the TR epithelium and was contiguous to VR, anchored by muscles. In the lumen, from one to three strata of sperm packets were observed, the dorsal one containing free sperm, and the most ventral stratum, spermatophores. An acidophilic glycoprotein layer enclosed the strata. Spermatophores in the ventral stratum were enclosed in a voluminous secretion, composed by acid polysaccharides most likely from the last male mated. The ventral‐type receptacle, stratified sperm packets, and polyandry, usually observed in females of Majoidea, suggest the occurrence of sperm competition in S. seticornis, favoring the sperm of the last male mated, as its sperm mass is located near the opening of the female oviduct.